Implementasi Education Of Sustainable Development (ESD) Dalam Pengolahan Limbah Organik Menjadi Kompos - Framita, Rabecha Maros; Emiyati, Emiyati; Taufik, Muhammad; Purnawinata, Dody Tri; Kurniawan, Iwan; Yuliastuti, Weny (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2024)
This article discusses the implementation of sustainable education (Education for Sustainable Development, ESD) in managing organic waste in two schools, SMPN 1 Lawang Kidul and SMPN 1 Ujan Mas. Activities include material counseling, compost making practices, as well as evaluation using pretest and posttest methods to measure increases in student knowledge. The results showed a significant increase in students' knowledge level after the activity. Of the 30 participants at SMPN 1 Lawang Kidul, there was an increase of 121%. Meanwhile, the 37 participants at SMPN 1 Ujan Mas achieved an average increase in knowledge of 42.78%. This is because students at SMPN 1 Ujan Mas have higher initial knowledge abilities compared to students at SMPN 1 Lawang Kidul. This research highlights the importance of ESD in increasing students' environmental awareness and making a positive contribution to organic waste management practices in schools.